Chemical Pretreatment of Lignocellulosic Biomass for the Production of Bioproducts: An Overview - Faiz Norrrahim, Mohd Nor; Ilyas, Rushdan Ahmad; Nurazzi, Norizan Mohd; Asmal Rani, Mohd Saiful; Nur Atikah, Mahamud Siti; Shazleen, Siti Shazra (Applied Science and Engineering Progress, 2021)
Lignocellulosic biomass has attracted great interest from researchers. It was due to the abundance of this valuable material which can be converted into value-added materials such as nanocellulose, biocomposites, bioelectricity, biohydrogen and biosugars. Lignocellulosic biomass is consisting of the three major components which are cellulose, hemicellulose and lignin. In order to utilize lignocellulosic biomass for bioproducts manufacturing, they need to be pretreated prior to further processing. Pretreatment can be carried out either by mechanical, chemical, biological or combination of all these methods. Chemical pretreatment is the common method used to pretreat the lignocellulosic biomass in order to completely or partially remove the components. During the past few years, a large number of chemical pretreatment including lime, acid, steam explosion, sulfur dioxide explosion, ammonia fiber explosion, ionic liquid and others have been discovered to be efficient pretreatment of biomass. Several types of chemical pretreatment of fibers and their future direction and also challenges were tackled in this review. This review could be beneficial for future directions in the pretreatment of fiber for the development of several products.